Association of Polymorphisms in the Period3 (turPer3) Gene with Growth and Reproductive Traits in Turkeys (Meleagris gallopavo) - Adikari , A.M.J.B.; Xu, J.; Smith, E.J. (International Journal of Poultry Science, 2018)
Background and Objective: Biological clock controls behavioral, physiological and biochemical circadian rhythms of animals. Circadian clock genes including period3 are involved in the circadian clock mechanism. The present study was conducted to test the hypothesis that differences in DNA sequence variations of the turkey period3 (turPer3) gene may be associated with performance traits including growth and reproduction. Methodology: The turPer3 gene was screened for DNA sequence variations and evaluated the relationships among haplogroups with performance traits. The DNA sequences of turPer3 (16.6 kb) gene were screened using 290 turkey birds by re-sequencing the individual amplicons. Results: Seven SNPs, including one each in exon 18 and intron 5, two SNPs in exon 19 and three SNPs in intron 6, were detected. The SNPs detected in the exon 19 were non-synonymous, which changed the amino acids from methionine to threonine and serine to phenylalanine at 953rd and 955th positions, respectively. Linkage disequilibrium (D’) among SNPs ranged from 0.03-1.00. Pairwise FST ranged from 0.01-0.43. Haplogroup frequencies of the turPer3 ranged from 0.02-1.00, were significantly associated with body weight (BW) at 231 days of age, average daily gain (ADG) for the period of 160-231 d of age, FCR for the periods of 69-159 d and 160-231 d, egg production and semen quality traits (p≤0.05). Conclusion: The DNA sequence variations of turPer3 gene are significantly associated with BW, ADG, FCR, egg production, egg weight and semen quality traits. turPer3 gene may seem to have some regulatory role in the molecular mechanism of the circadian clock. Genomic reagents reported in the present study would be valuable for future genotype: phenotype evaluation studies in the turkey using a candidate gene approach.